Jewish Persecutions and Weather Shocks: 1100–1800. (1st September 2016) - Anderson, Robert Warren; Johnson, Noel D.; Koyama, Mark
Abstract : What factors caused the persecution of minorities in pre‐modern Europe? Using panel data consisting of 1, 366 persecutions of Jews from 936 European cities between 1100 and 1800, we test whether persecutions were more likely following colder growing seasons. A one standard deviation decrease in growing season temperature in the previous five‐year period increased the probability of a persecution by between 1 and 1.5 percentage points (relative to a baseline of 2%). This effect was strongest in weak states and with poor quality soil. The long‐run decline in persecutions was partly attributable to greater market integration and state capacity.